2011
DOI: 10.1111/j.1439-0434.2011.01861.x
|View full text |Cite
|
Sign up to set email alerts
|

Possible Host Adaptation as an Evolution Factor of Cowpea aphid‐borne mosaic virus Deduced by Coat Protein Gene Analysis

Abstract: Cowpea aphid‐borne mosaic virus (CABMV) causes major diseases in cowpea and passion flower plants in Brazil and also in other countries. CABMV has also been isolated from leguminous species including, Cassia hoffmannseggii, Canavalia rosea, Crotalaria juncea and Arachis hypogaea in Brazil. The virus seems to be adapted to two distinct families, the Passifloraceae and Fabaceae. Aiming to identify CABMV and elucidate a possible host adaptation of this virus species, isolates from cowpea, passion flower and C. ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Although the plants had not been inoculated, several studies reveal that the high levels of identity with CABMV observed in the Brazilian isolates suggested that most PWD cases reported in Brazilian passion fruit were caused by CABMV, (Nascimento et al, 2006;Pinto et al, 2008;Cerqueira-Silva et al, 2008;Nicolini et al, 2012;Santos et al, 2015a;Carvalho, 2019) thus implicating CABMV as the cause of the disease and consequent economic losses in Brazil.…”
Section: Resultsmentioning
confidence: 99%
“…Although the plants had not been inoculated, several studies reveal that the high levels of identity with CABMV observed in the Brazilian isolates suggested that most PWD cases reported in Brazilian passion fruit were caused by CABMV, (Nascimento et al, 2006;Pinto et al, 2008;Cerqueira-Silva et al, 2008;Nicolini et al, 2012;Santos et al, 2015a;Carvalho, 2019) thus implicating CABMV as the cause of the disease and consequent economic losses in Brazil.…”
Section: Resultsmentioning
confidence: 99%
“…and common bean (Phaseolus vulgaris L.), have been reported. Those with the most predominance in the field are cucumber mosaic virus (CMV) (Eiras et al 2004), cowpea aphid-borne mosaic virus (CABMV) (Nicolini et al 2012), cowpea severe mosaic virus (CPSMV) (Abreu et al 2012) and cowpea mild mottle virus (CPMMV) (Lamas et al 2017). There are, however, few reports of viruses infecting lima bean (Carvalho et al 2015), possibly because lima bean is mainly cultivated by small farmers and has less economic importance than cowpea and common bean.…”
Section: Introductionmentioning
confidence: 99%
“…Passion fruit is a fruit crop cultured in Brazil, that is also affected by virus diseases which have adversely affected its production and expansion (FISCHER;KIMATI;RESENDE, 2005;NICOLINI et al, 2012). Several virus species have already been identified causing disease on passion fruit in Brazil and species from the genus Potyvirus have been considered to be responsible for the most important problems (LIMA et al, 2015;MACIEL et al, 2009).…”
Section: Introductionmentioning
confidence: 99%